In-service education program of elementary school teachers in the Philippines and its implication for Afghanistan - Amin, Aminullah (s.n.], 1970)
The purpose of the study is to examine in-service training for primary school teachers in the Philippines and to draw implications for Afghanistan. The study presents an analysis of the aspects of in-service training programs such as administration and finance, organization, curriculum, methods of teaching and evaluation of in-service training programs in the Philippines.